Body Shape Questionnaire (BSQ): Factorial structure and reliability in Peruvian university students - Baños-Chaparro, Jonatan (2020)
Body dissatisfaction is disspleasure with the appearance or size of some parts of the body and high levels of prevalence have been evidenced in the university population that constantly worries about their physical image. Therefore, the study sought to analyze the validity process based on the structure and internal consistency of the BSQ in a sample of university students. The research is of type instrumental and 272 women were evaluated using the BSQ. By means of a confirmatory factor analysis checked that the one-dimensional model explained the construct better compared to the models proposed by other studies. Furthermore, evidenced excellent internal consistency and of construct by means of the ω and H coefficients. The results support the use of the BSQ in the university population and its one-dimensional structure. Furthermore, the importance of evaluating body dissatisfaction in university students is highlighted.